2019
DOI: 10.1111/jnu.12503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Structured Nurse Leader Rounds on Satisfaction With Nursing Care Among Patients With Cancer

Abstract: Background The patient satisfaction rate is considered a challenge for nurse leaders, especially among patients with cancer, due to the complexity of the disease, diagnostic procedures, and treatment. Aim The purpose of this study was to evaluate the impact of structured nurse leader rounds (NLRs) on satisfaction with nursing care among patients with cancer. Moreover, we assessed the relationship among NLRs, patient satisfaction, and demographical variables. Methods A two‐group posttest design was used in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…About the other aspects of the quality of care, information accessibility ( p = .001), discharge instructions ( p = .001), coordination of care after discharge ( p = .001), and patients' experience with nurses' concern and caring ( p = .042) were significantly higher in the group of patients exposed to the NMIR (Ayaad et al, 2019). A significant difference after rounding was found in 1‐year post‐implementation with regards to communication with doctors (+11.5%, p = .007), pain management (+11.9%, p = .045), unit cleanliness (+10.1%, p = .027) and quietness (+8.3%, p = .049), whereas in 3‐year postimplementation, significant improvements emerged in communication with nurses (+4.8%, p = .025), communication about medication (+7.8%, p = .018) and discharge information (+5.1%, p = .032) (Manss, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About the other aspects of the quality of care, information accessibility ( p = .001), discharge instructions ( p = .001), coordination of care after discharge ( p = .001), and patients' experience with nurses' concern and caring ( p = .042) were significantly higher in the group of patients exposed to the NMIR (Ayaad et al, 2019). A significant difference after rounding was found in 1‐year post‐implementation with regards to communication with doctors (+11.5%, p = .007), pain management (+11.9%, p = .045), unit cleanliness (+10.1%, p = .027) and quietness (+8.3%, p = .049), whereas in 3‐year postimplementation, significant improvements emerged in communication with nurses (+4.8%, p = .025), communication about medication (+7.8%, p = .018) and discharge information (+5.1%, p = .032) (Manss, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated the HCAHPS mean score outcomes at pre-and post-rounding intervention (Cody & Williams-Reed, 2018;Hudson-Covolo et al, 2018;Manss, 2017;Winter & Tjiong, 2015). The remaining three also evaluated the post-test after the rounding intervention (Ayaad et al, 2019;Morton et al, 2014;Pattison et al, 2017).…”
Section: Rounding Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the implementation of nursing leader rounds had a significant impact in increasing patient satisfaction with patient and family involvement, patient discharge processes and care coordination, staff performance, responsiveness, and interaction with patients (Ayaad et al, 2019). By practicing the nursing round, it ensure that the patient feels cared for by the nursing staff while in the hospital, and increase nurse-patient interaction, satisfaction, and results (East et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The research that contributed to this study was mostly a qualitative study and a quasy-experiment. Research from the reviewed studies was conducted in seven different countries, Australia (Flowers et al, 2016;Tobiano et al, 2019;East et al, 2020), United States (Blakley, Kroth and Gregson, 2011;Daniels, 2016;), Iran (Negarandeh, Hooshmand Bahabadi, and Aliheydari Mamaghani, 2014), Republic of Korea (Shin and Park, 2018), Saudi Arabia (Saleh et al, 2011), United Kingdom (Kirk and Kane, 2016), and Jordan (Ayaad et al al., 2019). Nursing rounds in the journals article used in this reviewed are implemented in a treatment room or ward that have patients with different diagnoses and some are implemented in special care environments such as medical surgery units, emergency departments, oncology units, intensive care units (ICU), elderly care unit and maternity.…”
Section: Study Characteristicsmentioning
confidence: 99%